Dietary cholesterol-induced changes of protein kinase C and the effect of vitamin E in rabbit aortic smooth muscle cells - KARTAL ÖZER, NESRİN; ŞİRİKÇİ, ÖNDER (ELSEVIER IRELAND LTD, 1996)
The changes occurring in smooth muscle cells during the development of atherosclerosis in rabbits fed 2% cholesterol and the effect of vitamin E treatment were investigated. Ex-vivo smooth muscle cells obtained from the aorta of cholesterol-fed rabbits exhibited a 2-fold increase of protein kinase C expression and activity. The cholesterol induced changes in protein kinase C were equally present in the membrane bound and cytosolic fraction of the enzyme. The amount of a control protein cc-actin was not affected in smooth muscle cell by the high cholesterol diet treatment, indicating that protein kinase C increase was specific. The increase of protein kinase C expression and activity was not significantly affected by vitamin E treatment although a constant trend was noted. The data are discussed in the light of previous smooth muscle cell in vitro experiments.
Keywords: atherosclerosis; vitamin E; protein kinase C; smooth muscle cells; LOW-DENSITY-LIPOPROTEIN; D-ALPHA-TOCOPHEROL; CARDIOVASCULAR-DISEASE; E CONSUMPTION; ATHEROSCLEROSIS; PROLIFERATION; INHIBITION; ARTERIOSCLEROSIS; PATHOGENESIS; LESIONS